Vampire: A Smart Energy Meter for Synchronous Monitoring in a Distributed Computer System - Díaz, Antonio F.; Prieto, Beatriz; Escobar, Juan José; Lampert, Thomas (Journal of parallel and distributed computing, 2024)
•Design of a smart low-cost energy meter as an Internet of Energy (IoE) device.•How to measure energy performance on distributed and heterogeneous computers.•Energy consumption in parallel programming must be considered as a design parameter. This paper presents the design and implementation of a low-cost system oriented to the synchronised and real-time surveillance and monitoring of electrical parameters of different computer devices. To measure energy consumption in a computer system, it is proposed to use, instead of a general-purpose wattmeter, one designed ad-hoc and synchronously collects the energy consumption of its various nodes or devices. The implementation of the devised system is based on the confluence of several technologies or tools widely used in the Internet of Things. Thus, this article the intelligent objects are the power meters, whose connections are based on the low-cost ESP32 microcontroller. The message transmission between devices is carried out with the standard Message Queuing Telemetry Transport (MQTT) protocol, the measurements are grouped in a database on an InfluxDB server that store the sensor data as time series, and Grafana is used as a graphical user interface. The efficiency of the proposed energy monitoring system is demonstrated by the experimental results of a real application that successfully and synchronously records the voltage, current, active power and cumulative energy consumption of a distributed cluster that includes a total of 60 cores.